Avaliação da qualidade final de juntas dissimilares de ligas de alumínio 2024-6056 e 7075-6056 soldadas por FSW - friction stir welding - Potomati, Fernanda (Universidade Federal de São Carlos, 2006)
The aeronautic industry has been studying the FSW (Friction Stir Welding) process since its development by TWI (The Welding Institute), in 1991. Nowadays it has been used in the airplanes fuselage of the Eclipse Aviation Co. and in non structural parts of the Airbus A380, in recent times started. Thus, the knowledge on welding of aeronautic aluminum alloys is very important to give safety in the use of the process and to development of new possibilities of joints for these alloys. Dissimilar welding allows some freedom on project design i.e. possibilities to join materials with different properties. The challenge of this work is to join materials with different mechanical properties using FSW, which is based on mechanical deformation. For this aim, dissimilar joints, 2024-T351 to 6056-T4 and 7075-T76 to 6056-T4, have been welded. The rotational speed was maintained constant and the travel speed was variable. The best parameters were identified according to the final quality of the welds after microstructural analyses and mechanical properties evaluation (tensile and microhardness tests). The analyses of the thermal cycles and forces developed during the weld, and the evaluation of the quality weld determine the best parameters that can produce a better combination between heat input and the best weld quality. It is concluded that the mechanical properties of the dissimilar joints improve with increasing weld travel speed and when the 6056 alloy is placed in the advancing side of the joint.
Evaluation of dissimilar joints of aluminum alloys 2024-6056 and 7075-6056 friction stir welded
Keywords: Soldagem; Soldagem de estado sólido; Ligas de alumínio; Microestrutura; Propriedades mecânicas; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA